Temporal trends of transcatheter aortic valve implantation practice in South Africa - Mwase, T; Doubell, AF; Weich, H; Schaafsma, E; Ngarande , E; Ntsekhe, M; Tsabedze, N; Scherman, J (SA Heart Journal, 2026)
Background: The temporal trends in transcatheter aortic valve implantation (TAVI) practice and procedural benefits are well documented in high-income countries; however, data for upper-middle-income countries (UMIC) are sparse. Objectives: This study aimed to describe the evolution of TAVI practice in South Africa, including patient and procedural characteristic profiles and outcomes, from 1 September 2014 to 31 December 2023. Methods: The South African Heart Association (SHARE)-TAVI registry is a web-based, all-comers prospective registry. The 18 centres that were involved from the outset of the registry in September 2014 were included in our analysis. Results: A total of 2 532 TAVIs were performed across the 18 centres. There was a steady increase in TAVI procedures, with most performed in private hospitals (n = 2 251). Waiting times were shorter in the private hospitals, with a median of 52 days (interquartile range [IQR] 29–82), compared with public hospitals, with a median of 70 days (IQR 61–85). Over time, the median age remained stable at 81 years (IQR 75–85). The European System for Cardiac Operative Risk Evaluation (EuroSCORE) II showed a continuous and significant decline from 4.9% (IQR 4.4, 8.6) in 2014/15 to 3.5% (1.9, 6) in 2023 (p < 0.001). Transfemoral access was the most prevalent access route utilised throughout the study period, and there was a trend of increased use of percutaneous closure devices with lower vascular complications (11% in 2014/15 to 5% in 2023; p < 0.001). There was also a notable reduction in periprocedural strokes (10% in 2014/15 to 2% in 2023; p < 0.0001). Kaplan-Meier survival curves showed a gradual decrease in mortality risk (p = 0.0344). Accordingly, the 1-year mortality fell from 17% in 2014/15 to 6% in 2022 (p < 0.001). Conclusion: This data showed a steady increase in the number of TAVI procedures during the study period, with a reduction in risk profiles despite the mean age remaining stable, consistent with international recommendations. Technical aspects of the procedures evolved and were associated with reduced complications.